2011
DOI: 10.4088/pcc.10br01006
|View full text |Cite
|
Sign up to set email alerts
|

Acute Psychosis and Type 2 Diabetes Mellitus: Should Screening Guidelines Be Revised?

Abstract: Although psychosis increases the risk for developing type 2 diabetes, the temporal relationship between the onset of psychosis and the onset of diabetes has not been studied. We present 6 cases of acute psychosis, which led to the new diagnosis of type 2 diabetes during inpatient psychiatric admission within days to weeks of the psychotic episode. The implications of these findings and the efficacy of current diabetes screening guidelines are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Recent studies found that the disruption of glucose-insulin homeostasis may presage psychosis ( 49 ), and that insulin resistance is related to pre-psychotic symptoms in young individuals before the onset of clinical psychosis ( 50 ). One case report linked hyperglycemia to psychotic symptoms, and a case series showed that poor blood glucose management may have been connected to psychosis ( 51 , 52 ), particularly as increased insulin is associated with mood alteration ( 53 ). Psychiatric patients have a high prevalence of hyperglycemia and diabetes, late diagnosis, poor somatic management ( 54 , 55 ) and non-adherence to somatic treatment ( 56 ), which may lead to psychosis or relapse and readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that the disruption of glucose-insulin homeostasis may presage psychosis ( 49 ), and that insulin resistance is related to pre-psychotic symptoms in young individuals before the onset of clinical psychosis ( 50 ). One case report linked hyperglycemia to psychotic symptoms, and a case series showed that poor blood glucose management may have been connected to psychosis ( 51 , 52 ), particularly as increased insulin is associated with mood alteration ( 53 ). Psychiatric patients have a high prevalence of hyperglycemia and diabetes, late diagnosis, poor somatic management ( 54 , 55 ) and non-adherence to somatic treatment ( 56 ), which may lead to psychosis or relapse and readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Lopes et al ​[ 9 ] reported a case of an 80-year-old woman with delirium and psychotic symptoms associated with hyperglycemia from poorly controlled type 2 diabetes mellitus (T2DM). On a related note, Bauer et al ​[ 10 ]​ presented a case series of six patients who were diagnosed with T2DM after being admitted for acute psychosis. The exact mechanism that relates psychotic episodes to hyperglycemia is still unknown, highlighting the need for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Poor lifestyle [3,[9][10][11] and second generation antipsychotic medication are known to favor the development of the metabolic syndrome and T2D [5,12,13]. Therefore, the screening for glucose abnormalities has been advocated to prevent their development and complications [14][15][16]. It is estimated that, among ISMI, up to 70 % of T2D cases are not diagnosed compared to 23-30 % in the general population [3].…”
Section: Introductionmentioning
confidence: 99%